Manajemen Pembiayaan Pendidikan di Sekolah Menengah Pertama Cokroaminoto Manado - Zelan Tamrin Danial (MASALIQ, 2025)
Although the management of education financing has been the focus of numerous previous studies, in-depth investigations into its practical implementation at the junior secondary school level remain limited. This study aims to explore the management of education financing at SMP Cokroaminoto Manado, with particular attention to the processes of planning, implementation, and evaluation of school fund utilization. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation during the research period from 6 to 21 May 2024. The primary informants included the Principal and the School Treasurer. The findings reveal that financing plans were developed based on actual data used in the preparation of the Rencana Kegiatan dan Anggaran Sekolah (RKAS). The Dana BOS served as the main funding source, with approximately 50% allocated for payment of honorary teachers, while the remainder supported school operational needs. Due to limitations in Dana BOS, the school relied on committee fund contributions to address budget shortfalls. The implementation phase demonstrated flexibility in adjusting to the school’s priority needs. Evaluation was conducted periodically through supervision, internal audits, and transparent reporting to stakeholders. These findings underscore the importance of data-driven planning and accountable fund management to ensure the effectiveness of education financing at the school level. The study’s implications support the reinforcement of school fund management policies based on transparency and school community participation.